2014
DOI: 10.1115/1.4028037
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Collagen Decreased Endothelial Cell Fibronectin Alignment in Response to Cyclic Stretch Via Interruption of Actin Alignment

Abstract: Hyperglycemia is a defining characteristic of diabetes, and uncontrolled blood glucose in diabetes is associated with accelerated cardiovascular disease. Chronic hyperglycemia glycates extracellular matrix (ECM) collagen, which can lead to endothelial cell dysfunction. In healthy conditions, endothelial cells respond to mechanical stimuli such as cyclic stretch (CS) by aligning their actin cytoskeleton. Other cell types, specifically fibroblasts, align their ECM in response to CS. We previously demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Devices that involve deformation of a cellular support membrane (Winston et al, 1989 ; Schaffer et al, 1994 ; Brown, 2000 ) are commonly used to study the effects of physiological strain on endothelial cells (Vion et al, 2013a ; Figueroa et al, 2014 ) and TBI-like injury on neurons and glial cells (Ellis et al, 1995 ; Geddes-Klein et al, 2006 ; Cullen et al, 2007 ). Only recently have these devices been used to model the effects of TBI on endothelial cells (Salvador et al, 2013 , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Devices that involve deformation of a cellular support membrane (Winston et al, 1989 ; Schaffer et al, 1994 ; Brown, 2000 ) are commonly used to study the effects of physiological strain on endothelial cells (Vion et al, 2013a ; Figueroa et al, 2014 ) and TBI-like injury on neurons and glial cells (Ellis et al, 1995 ; Geddes-Klein et al, 2006 ; Cullen et al, 2007 ). Only recently have these devices been used to model the effects of TBI on endothelial cells (Salvador et al, 2013 , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unglycated or glycated recombinant human collagen 1 was added to culture media in soluble form for 2D culture. For glycation, recombinant human collagen 1 (Rockland Immunochemicals, Inc., Limerick, PA, USA, Cat#009-001-103) was incubated in 100 ÎŒg/ml with 500 mM D-glucose-6-phosphate in PBS, 4 weeks, 37 °C, and used at 20 ÎŒg/ml in culture, based on previously published methods 69 , as well as dose response studies we performed studying concentrations ranging from 20–100 ÎŒg/ml that demonstrated 20 ÎŒg/ml provided maximal effect on adipocyte glucose uptake.…”
Section: Methodsmentioning
confidence: 99%
“…For faculty actively engaged in research, real-world context can also be found in research papers or in the laboratory. For example, the authors previously based problems on endothelial cell response to flow and cyclic strain in diabetic conditions [17,18]. These types of problems can be simple to create and implement, since faculty already ground their research in clinical problems, and the techniques and sample data are readily available.…”
Section: Introductionmentioning
confidence: 99%